Green and controllable synthesis of one-dimensional Bi2O3/BiOI heterojunction for highly efficient visible-light-driven photocatalytic reduction of Cr(VI). (October 2020) - Wei, Zhiping; Zheng, Nan; Dong, Xiaoli; Zhang, Xiufang; Ma, Hongchao; Zhang, Xinxin; Xue, Mang
Abstract: BiOI nanosheets have been successfully deposited on the porous Bi2 O3 nanorobs via a one-pot precipitation method. The physicochemical features of the as-prepared materials were characterized in detail by a series of techniques, and the results revealed that BiOI nanosheets were evenly distributed on the porous Bi2 O3 nanorobs. Because of higher photogenerated electron-hole pairs separation efficiency and the larger specific surface area compared to the pristine Bi2 O3 and BiOI, the 50%Bi2 O3 /BiOI composite exhibited significantly enhanced photocatalytic activity for Cr(VI) reduction under visible light irradiation, and the reduction rate constant was 0.02002 min −1, which was about 27.4 and 2.6 times higher than that of pure Bi2 O3 (0.00073 min −1 ) and BiOI (0.00769 min −1 ), respectively. Moreover, the 50%Bi2 O3 /BiOI composite also possessed the excellent photochemical stability and recyclability, thereby facilitating its wastewater treatment application. Graphical abstract: Image 1 Highlights: 1D Bi2 O3 /BiOI composites were fabricated via a novel one-pot precipitation method. All the solvents during synthesis were deionized water. Bi2 O3 /BiOI composites exhibited high photocatalytic Cr(VI) reduction activity. 1D Bi2 O3 /BiOI improved the separation efficiency of photogenerated charges.